Sex‐based differences in procedural complications associated with atrial fibrillation catheter ablation: A systematic review and meta‐analysis. (5th October 2020) - Campbell, Martin L.; Larson, John; Farid, Talha; Westerman, Stacy; Lloyd, Michael S.; Shah, Anand D.; Leon, Angel R.; El‐Chami, Mikhael F.; Merchant, Faisal M.
Abstract: Background: Women undergoing atrial fibrillation catheter ablation (AFCA) have higher rates of vascular complications and major bleeding. However, most studies have been underpowered to detect differences in rarer complications such as stroke/transient ischemic attack (TIA) and procedural mortality. Methods: We performed a systematic review of databases (PubMed, World of Science, and Embase) to identify studies published since 2010 reporting AFCA complications by sex. Six complications of interest were (1) vascular/groin complications; (2) pericardial effusion/tamponade; (3) stroke/TIA; (4) permanent phrenic nerve injury; (5) major bleeding; and (6) procedural mortality. For meta‐analysis, random effects models were used when heterogeneity between studies was ≥50% (vascular complications and major bleeding) and fixed effects models for other endpoints. Results: Of 5716 citations, 19 studies met inclusion criteria, comprising 244, 353 patients undergoing AFCA, of whom 33% were women. Women were older (65.3 ± 11.2 vs. 60.4 ± 13.2 years), more likely hypertensive (60.6% vs. 55.5%) and diabetic (18.3% vs. 16.5%), and had higher CHA2 DS2 ‐VASc scores (3.0 ± 1.8 vs. 1.4 ± 1.4) ( p < .0001 for all comparisons). The rates of all six complications were significantly higher in women. However, despite statistically significant differences, the overall incidences of major complications were very low in both sexes: stroke/TIA (women 0.51% vs. men 0.39%) and procedural mortality (women 0.25% vs. men 0.19%). Conclusion: Women experience significantly higher rates of AFCA complications. However, the incidence of major procedural complications is very low in both sexes. The higher rate of complications in women may be partially attributable to older age and a higher prevalence of comorbidities at the time of ablation. More detailed studies are needed to better define the mechanisms of increased risk in women and to identify strategies for closing the sex gap.